Model Kolaborasi Pengembangan Geopark Bayah Dome - Mas Moch Fathahillah (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2022)
A geopark is a geographical area that has a prominent geological heritage site and is part of a holistic concept of protection, education and sustainable development. Geoparks do not only include geological sites, but also have clear geographical boundaries and the synergy between the geological, biological, and cultural diversity that exists within the area. Communities living in the legacy play a role in protecting and enhancing the function of the natural heritage. The purpose of this research is to describe a collaboration model that is in accordance with the conditions in the development process of the Bayah Dome Geopark. This research is a descriptive research with a qualitative approach. Qualitative research was conducted because this research requires in-depth information with the aim of identifying the roles of collaborative actors in the development of the Bayah Dome Geopark. This study uses descriptive research in order to determine the Bayah Dome Geopark Development Collaborative Model which involves many stakeholders. The results of this study are that there are 8 collaborative processes that occur in the development of the boyah dome geopark, namely: (1) Network Structure, (2) Commitment To Common Purposes, (3) Trust Among Participants, (4) Governance, (5) Access To Authority, (6) Distributive Accountability, (7) Access To Resources, (8) Information Sharing.